BORTEZOMIB INDUCED SUBCONJUNCTIVAL HEMORRHAGE - Patil, Navin; Ommurugan, Balaji; Udupa, Karthik S; Rao, Karthik (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Many drugs are used in the treatment of multiple myeloma but Thalidomide, Lenalidomide, Bortezomib, dexamethasone and their combination remains the main stay of treatment. The molecular formula of bortezomib is C19H25BN4O4 and its chemical IUPAC name is [3-methyl-1-(3-phenyl-2-pyrazin-2-ylcarbonylamino-propanoyl) amino-butyl] boronic acid. Mechanisms by which it acts is usually by 26 SProteasome inhibition leading to degradation of anti-apoptotic proteins. Bortezomib is known to cause many side effects. So hence we report a rare case of Bortezomib induced subconjunctival hemorrhage in our tertiary care hospital. KEYWORDS: Bortezomib, Adverse effect, Proteosome inhibition, Subconjunctival Hemorrhage